Single and multiple antenna relay-assisted techniques for uplink and downlink OFDM systems - Moço, Andreia (2012)
In this paper we propose and assess the performance of relay-assisted schemes designed for both the uplink and downlink OFDM based systems, using efficient distributed space-frequency block coding protocols. We consider the use of an antenna array at the base station and a single antenna at the user terminal. At the relay node we consider either single antenna or an antenna array. We assume that some of the user terminals deployed in a certain area could act as relaying-able terminals for the communication of other users. Two types of relay-assisted protocols are considered: equalize-and-forward and decode-and-forward. The optimal maximum ratio combining coefficients are derived for the proposed relay-assisted schemes. The performance of these cooperative schemes is evaluated under realistic scenarios, considering typical pedestrian scenarios based on WiMAX specifications and using channel convolutional turbo code. The proposed schemes are also compared against the non-cooperative OFDM based systems. +umerical results show that the availability of antenna arrays at the relays significantly improves the cooperative systems performance, which outperform the non-cooperative ones in most studied scenarios.